ChemInform Abstract: Arene CH—O Hydrogen Bonding: A Stereocontrolling Tool in Palladium‐Catalyzed Arylation and Vinylation of Ketones. Issue 37 (22nd August 2013) - Huang, Zhiyan; Lim, Li Hui; Chen, Zuliang; Li, Yongxin; Zhou, Feng; Su, Haibin; Zhou, Jianrong
Abstract Different enol acetates are treated with aryl and vinyl triflates as well as aryl halides in the presence of chiral phenoxy‐substituted ligands (I).